Estudo do processo de decomposição térmica do glicerol - Leitão, João Igor da Rocha (2014)
Biodiesel production has grown to supply demands from the transport and power generation systems increasing steadily. In general, in this production process, the glycerol is the main waste, resulting from the transesterification of vegetable oils or animal fats utilized. In this paper, a gasification alternative for thermal decomposition of glycerol is proposed, aiming the production of synthesis gas (CO + H2) and other substances that have higher added value, based on the porous bed combustion technology, which is constituted of alumina spheres (Al2O3) in order to act as a heat recirculating medium, preventing the energy release by gas exhaustion. The porous bed responds well to thermal decomposition of glycerol to achieve maintaining high and uniform temperature throughout the body of the reactor, avoiding the production of toxic products, such as acrolein (C3H4O), which is formed at temperatures around 280 °C. The medium formed by alumina particles creates an environment in which the mechanisms of heat transfer by conduction and convection are optimized due to the presence of the porous bed, which prevents the formation of cold zones that can eventually lead to the formation of these toxic elements. The focus of this research is the investigation of the mechanism of thermal decomposition of glycerol in the production of syngas and other substances of economic interest. For this work, the AspenTech software was utilized as well as a thermal decomposition reactor, built with characteristics proper to perform the gasification of biomass. This experimental apparatus consists of a gasification reactor with multiple heating stages, supported by a simplified modeling, performed for each temperature level throughout the body of the reactor.